PENGARUH METODE PENYULUHAN TERHADAP PENGETAHUAN DAN SIKAP TENTANG BAHAYA KABUAT ASAP BAGI KESEHATAN (STUDI PADA SISWA SMA MUHAMMADIYAH KABUPATEN SINTANG) - Juliansyah, Elvi (JURNAL BORNEO AKCAYA, 2021)
ABSTRACT Forest and land fires cause an increase in pollutants due to smoke from forest fires that are harmful to health, especially causing ARI. This study was to determine the effect of health education on the dangers of smoke on the knowledge and attitudes of students at SMA Muhammadiyah Sintang. The research applied quantitative method with a pre-experimental approach, one group pre-test and post-test. The research sample was taken using the convenience sample technique. The results showed that the education on the dangers of smog for health could increase the students' knowledge by 5.51 from 30.69, to 36.20. The results of the t-test obtained p value = 0.046 statistically; there was a significant difference in knowledge. Counseling on the dangers of smog for health reduced the positive attitude of students by 1.62 from 35.64 to 34.02. The results of the t-test obtained p value = 0.027, meaning that there was a statistically significant difference in attitudes. In conclusion, the counseling can be carried out continuously in a planned manner so that the students' knowledge about the risks of exposure to smoke haze and the student attitudes support the health education programs.